Predictive Factors for Hypotension Associated With Supine-to-Prone Positional Change in Patients Undergoing Spine Surgery. Issue 2 (April 2020) - Yoon, Hyun-Kyu; Lee, Hyung-Chul; Chung, Jaeyeon; Park, Hee-Pyoung
Abstract : Background: Positional change during general anesthesia can cause hypotension. The objective of this retrospective study was to determine predictive factors for hypotension associated with supine-to-prone positional change in spinal surgery patients. Materials and Methods: Data on demographics, current medications, comorbidity, intraoperative mean arterial pressure (MAP), heart rate, pulse pressure variation, tidal volume, peak inspiratory pressure, and propofol and remifentanil effect-site concentrations were collected from 179 patients undergoing elective spine surgery. Hypotension associated with supine-to-prone positional change was defined as >20% reduction in MAP during positional change. Results: Hypotension associated with supine-to-prone positional change was observed in 16 (8.9%) patients. The median (interquartile range) effect-site concentration of remifentanil (5.3 [4.0 to 8.5] vs. 4.0 [3.1 to 4.0] ng/mL, P <0.001), MAP (95.0 [86.0 to 103.5] vs. 80.0 [70.0 to 94.0] mm Hg, P =0.014), peak inspiratory pressure (16.5 [15.0 to 18.5] vs. 15.0 [14.0 to 17.0] hPa, P =0.040) in the supine position, and pulse pressure variation in the prone position (12.0 [9.0 to 16.4] vs. 9.0 [7.0 to 12.0]%, P =0.019) were significantly higher in the hypotension group. In multivariate logistic regression analysis, the effect-site concentration of remifentanil (odd ratio [95% confidence interval], 2.12 [1.51-2.96], P <0.001), preoperative use of beta-blocker (7.64 [1.21-48.36], P =0.031), and MAP in the supine position (1.04 [1.00-1.07], P =0.033) were independent predictive factors for hypotension associated with supine-to-prone positional change. Conclusions: Increased effect-site concentration of remifentanil, preoperative use of beta-blocker, and high MAP in the supine position were predictive factors for hypotension associated with supine-to-prone positional change in spinal surgery patients.